1985
DOI: 10.1002/jso.2930290202
|View full text |Cite
|
Sign up to set email alerts
|

Use of 111in‐bleomycin for combining radiotherapy and chemotherapy on glioma‐bearing mice

Abstract: Mice bearing transplanted glioma received 0.9% NaCl, 0.1 mg of BLM, or 200-250 microCi of 111In-BLM (0.1 mg BLM) daily for 5 days intraperitoneally. After therapy, tumor sizes were in the order NaCl greater than BLM greater than 111In-BLM. On the 11th day after the first injection, tumor size (mm3) in the 111In-BLM group was 1,220; in the BLM group, it was 2,310 (P less than .025). After intratumor injection of a total dose of 0.1 mg of BLM/gm tumor weight, or of 1 mCi/gm tumor weight of 111In-BLM (carried by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The cytotoxicity of 111 In-BLMC has been demonstrated in human small cell lung cancer and head-and-neck carcinoma cell lines [120][121][122]. Moreover, in glioma-or head-and-neck-tumour xenograft bearing nude mice, 111 In-BLMC diminished tumour size better than unlabelled BLMC [123][124][125]. 111 In-BLMC is stable in vitro and in vivo and because it does not bind to transferrin, it does not cause toxicity to the bone marrow [117,[126][127][128].…”
Section: In-bleomycin 111mentioning
confidence: 99%
“…The cytotoxicity of 111 In-BLMC has been demonstrated in human small cell lung cancer and head-and-neck carcinoma cell lines [120][121][122]. Moreover, in glioma-or head-and-neck-tumour xenograft bearing nude mice, 111 In-BLMC diminished tumour size better than unlabelled BLMC [123][124][125]. 111 In-BLMC is stable in vitro and in vivo and because it does not bind to transferrin, it does not cause toxicity to the bone marrow [117,[126][127][128].…”
Section: In-bleomycin 111mentioning
confidence: 99%
“…Our results in animal experiments and gel electrophoresis indicate that '' 'In-BLM [4], ' "In-BLM-A2, or -B2 [5] were stable in vivo and that "'In-BLM was an effective compound for therapy of mouse glioma [6]. However, this conventional ' I 'In-BLM binds to transferrin, which is distributed throughout the body such that the ' ' In-BLM yield a high whole body dose, thereby limiting its practical value in the clinic.…”
Section: Introductionmentioning
confidence: 80%
“…22 The binding of indium-111 labeled bleomycin complex ( I I I In-BLMC) has been studied in mice tumors and cell lines. 23 The initial distri -b u t i o n o f t 1 I In-BLMC is reported to be similar to that of cobalt-labeled bleomycin with a fast clearance from the blood into other organs and tissues, an early uptake in the kidneys, and excretion of a large part during the first 24-48 h. 24,25 Recently radiolabeled bleomycin complexes have been used as tracers in the diagnosis and staging of human head and neck cancers. 26 Huhmar et al 27 have preliminarily reported ... In-BLMC to be a useful SPECT tracer for the grading of human gliomas.…”
Section: Introductionmentioning
confidence: 99%